A Review on Mechanical Properties of 3D Print Concrete Incorporating Recycled Fine Aggregate (RFA) - Ahmad Budin, Adrin; Seyed hakim, Seyed jamalaldin (Recent Trends in Civil Engineering and Built Environment, 2024)
3D print concrete is an emerging construction technology, and presents an opportunity for utilising materials that are otherwise considered unsuitable for concrete construction. Incorporating recycled fine aggregates from construction and demolition waste can preserve natural aggregate resources and contribute to sustainable built environment. However, the RFA as construction material in concrete mix of 3DPC is seldom applied compared to natural aggregate as construction material. Hence, this study provides a comprehensive review on the mechanical properties and structural performance of RFA, to investigate the suitability of this material to be used as construction materials. The different strategies and parameters on the behavior of 3DPC incorporating RFA such as the set-up and equipment, process, material requirement, and 3DPC parameters were determined. Moreover, the compressive strength and flexural strength are the important mechanical properties to determine the performance of 3DPC structures. Thus, the effect of 3DPC incorporating RFA on those mechanical properties and structural behavior was investigated from several journals, research paper through peer review study of the experiment and analysis will be make based on its shrinkage and failure pattern characteristics. RFA is expected to have lower compressive and flexural strength, compared to natural aggregate but the difference is not significant. RFA concrete can be used in 3DPC structures design. RFA concrete has an assured quality of practicality in compressive strength and flexural strength without significant effect on strength of concrete.